Pengaruh Promosi Penjualan dan Tagline Terhadap Keputusan Pembelian Konsumen Tokopedia - Djiepangestu, Erfan; Iskandar, Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2023)
This research is aims to find out how the influence of sales marketing and taglines on consumer purchasing decisions at Tokopedia. By discussing how companies can attract people to use the Tokopedia application as a shopping application. This type of research is a causal conclusive research where this study aims to obtain evidence of a causal relationship between sales promotion variables and taglines on purchasing decisions on sales in the Tokopedia application. This research uses quantitative research. The results of this study indicate that sales promotions have a positive but not significant effect on Tokopedia's consumer purchasing decisions. The results also show that promotion has a positive and significant influence on purchasing decisions.